Validitas Perangkat Pembelajaran Model Flipped Classroom dalam Meningkatkan Motivasi dan Hasil Belajar Kognitif Siswa SMA - Jodion Siburian; Anggun Br Sihotang; Ali Sadikin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Learning devices play an important role in directing the implementation and learning process. Before being used, all learning tools must be properly prepared according to the needs of the implementation of the learning model. The implementation of the flipped classroom learning model is one of the expected learning alternatives and motivates students to learn optimally and expects that student learning outcomes can also increase. Prior to implementation, it is necessary to develop better devices and conduct a feasibility analysis of the developed devices. The research was conducted at SMA N 1 Jambi City. This type of research is descriptive quantitative using data collection techniques in the form of closed questionnaires. The research aspects included syllabus validation, lesson plans, pretest and posttest question sheets, worksheets and student learning motivation questionnaires. Data analysis uses the percentage comparison between the score obtained and the maximum score. The results of the validator's assessment of the syllabus, lesson plans, worksheets, pretest and posttest questions, as well as the student learning motivation questionnaire were 82.25%; 83.25%; 80%; 86% and 86% in the